Nanomaterial‐Based Electrochemical Sensors: Mechanism, Preparation, and Application in Biomedicine. Issue 6 (8th April 2021) - Liu, Xun; Huang, Lin; Qian, Kun
Abstract : Nanomaterials possess unique properties, including excellent electrochemical properties, high surface area, and tunable electric conductivity, making them attractive for sensing applications, especially for electrochemical sensing. Notably, the compatibility of nanomaterials with other techniques opens up opportunities for electrochemical sensors in various biomedical applications. Herein, the enhancing mechanisms and preparation protocols of electrochemical sensors, regarding the material choices, are introduced. The integration of nanomaterial‐based electrochemical sensors with other techniques toward precise health management and controlled drug release is further highlighted. It is concluded with perspectives on the future directions for this topic. Future research directions of nanomaterial‐based electrochemical sensors and the challenges faced by commercialized implementation of the sensors are presented, paving the way for the upcoming era of accurate biosensing toward both academic and industrial use. Abstract : Electrochemical biosensors are the analytical system of choice for rapid and on‐site test in biomedical practice. Nanomaterials with high electrical conductivity and electrocatalytic performance, are investigated in electrochemical biosensors to develop commercial products in clinical workflow. Herein, the latest progress in the field of nanomaterial‐enhanced electrochemical sensors with special emphasis on nanomaterial choices in biomedicines is reviewed.